Analisis Mitigasi Risiko dan Peningkatan Keselamatan Pejalan Kaki di Kawasan Pasar Induk Brebes - Iswatun Hasanah; Rachmat Mudiyono; Abdul Rochim (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2026)
Traditional market areas with high activity intensity create convergence of multiple traffic movements, leading to congestion and increased pedestrian-vehicle conflicts. This study aims to analyze risk mitigation and formulate strategies for improving pedestrian safety at the Pasar Induk Brebes using an integrated approach. A quantitative descriptive-evaluative method was applied, collecting data through traffic surveys, pedestrian facility audits, and questionnaires involving 110 respondents. Analysis covered traffic performance using MKJI 1997, pedestrian Level of Service (LOS), Walkability Index, inferential statistical tests (Mann–Whitney, Spearman, and Chi-Square), and SWOT analysis. Results show road segments operating at LOS B (V/C = 0.39) with high side friction, while the signalized intersection records DS > 1.0 on two main approaches. Pedestrian facilities are suboptimal: effective sidewalk widths of 2.5 m (east) and 1.2 m (west), LOS B–C at peak hours, and a PV² value of 2.33 × 10⁹ recommending a Pelican Crossing, yet no formal crossing facility currently exists. The Walkability Index averages 42.86 (marginal category). Mann–Whitney tests confirm significant gender-based perception differences (p < 0.05); Spearman correlation reveals a very strong relationship between traffic conflict and walkability index (ρ = 0.917, p < 0.001). SWOT-based strategies propose installation of Pelican Crossing, inclusive sidewalk rehabilitation, side friction management, and strengthened traffic enforcement.